Propriedades físico-químicas e avaliação sensorial de farinha mista de arroz e soja pré-cozida por extrusão - da Silva Cruz, Maria Júlia; Teixeira Coelho, Dilson; Kalagi Kibuuka, Godfrey; Paes Chaves, José Benício (Revista Ceres, 2025)
Rice flour, substituted up to 40% with defatted soy flour, was subjected to a hydrothermal extrusion process and the products analysed for both physico-chemical and organoleptic properties.